Análise do custo da triagem auditiva neonatal universal: estudo dos fatores predominantes - Fazion, Cíntia Bincoleto (2012)
This work aims to analyze the cost and benefit for three different protocols for Universal Newborn Hearing Screening, because since 2010, Otoacoustic Emissions should be applied to all newborns before hospital discharge, by law. For the study was done a combination of TOAE and AABR defined. Protocol 1: UNHS using TOAE, in two stages; protocol 2: UNHS using TOAE in the first stage and AABR in case of refer as a second stage, prior to the hospital discharge; protocol 3: UNHS the TOAE was used on newborns without Risk Indicators for Hearing Loss in the first stage and the AABR was used on those who did not pass the first test before medical discharge. For the infants with Risk Indicators it was used only AABR on both stages. It is noteworthy that all newborns who redid the tests were followed at the Hearing Health Center, which belongs to the university clinic. The protocols were analyzed under the National Center of Hearing Assessment and Management Proposal (2003). The obtained results showed that the actual costs ranged between R$ 36.74 and R$ 39.96, but the protocol 3, with a cost of R$ 39.93 per newborn screened was considered the most effective, since it could identify cochlear hearing loss in all neonates and auditory neuropathy in newborns at high risk. The benefits were analyzed using a theoretical approach. In conclusion we could verify that the Protocol 3 - using EOAT in infants without risk and AABR to at-risk infants, and a second phase with AABR-A for any baby who failed the first test - proved the most effective, although its cost is higher compared to the present Protocol 2